Computational Simulation of Comb-plate Expansion Joints - Liang Tang; Xiaoyan Zhang; Jian Tang; Wu Jie (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
A finite element model of the expansion Joints’ common damages of a novel comb-plate by using the finite element software ABAQUS is presented in this paper. The mechanical behavior of expansion Joints is analyzed to verify the weak parts of it. The research results provide a reference for the design of the comb-plate expansion Joints.